Progressive damage analysis of carbon fiber-reinforced additive manufacturing composites (2023)
Fiber-reinforced additive manufacturing (FRAM) is used in aeronautics, sports, and manufacturing. FRAM composites display better properties than AM polymers and better manufacturability than traditional composite manufacturing. However, their mechanical properties, damage behavior, and failure mechanisms are still active research topics because of their recent development. To assess its prediction capabilities, the present work aims to develop a progressive failure analysis of FRAM composites via the continuum damage mechanics (CDM) method. This approach relies on a reduced methodology, allowing few tests to determine the damage parameters. This work extends engineering design tools by assessing a damage method, estimating progressive damage and its link with damage variables. Previous works in damage mechanics of AM are scarce, requiring extensive experimentation and programming while this work presents a model with ease of implementation, yet accurate results. Progressive damage analysis is performed in continuous fiber-reinforced additive manufacturing parts with fiberglass, Kevlar reinforcements, and polymeric regions made of Onyx material, a chopped carbón fiber-reinforced polymer matrix composite. Results show that despite the large void fraction, configurable parameters, and degrees of freedom, CDM models are suitable for the progressive damage analysis of FRAM. Possible applications of this work could be in progressive damage failure analysis (PDFA) of FRAM, and also to enhance the design and optimization workflow with parts in aerospace, automotive, manufacturing, and biomedical sectors